Two promising Bacillus-derived antifungal lipopeptide leads AF4 and AF5 and their combined effect with fluconazole on the in vitro Candida glabrata biofilms - Madhuri, Madduri; Rudramurthy, Shivaprakash M.; Roy, Utpal (Frontiers in Pharmacology, 2024)
Candida species are endowed with the ability to produce biofilms, which is one of the causes of pathogenicity, as biofilms protect yeasts from antifungal drugs. Candida glabrata (Nakaseomyces glabrata) is one of the most prevalent pathogenic yeasts in humans and a biofilm producer. The study was aimed at evaluating the combined effects of two highly promising antifungal biomolecules (AF4 and AF5) lipopeptide in nature, chromatographically purified to homogeneity from Bacillus subtilis (B. subtilis) and the standard antifungal fluconazole (at different concentrations) to demonstrate C. glabrata biofilm formation inhibition. Biofilm production and inhibition were evaluated by quantification of the biofilm biomass and metabolic activity using crystal violet (CV) staining and XTT reduction assays, respectively. Microscopic techniques such as confocal scanning laser microscopy (CSLM) and scanning electron microscopy (SEM) were employed to visualize biofilm formation and inhibition. Compared to untreated and fluconazole-treated biofilms, an enhanced in vitro anti-biofilm effect of the antifungal lipopeptides AF4/AF5 alone and their combinations with Commented [Ma1]: Reviewer's suggestion has been incorporated in line number 19 revised manuscript.